Předcházení školní neúspěšnosti v diskurzu vyučujících 1. stupně ZŠ - Veronika Francová; Anna Páchová (Karolinum Press, 2024)
Strategies for supporting pupils at risk of school failure at the beginning of schooling process are the key to a successful educational process. The study is part of research aimed at preventing school failure in the first three years of schooling. The aim of the study is to identify categories of general support strategies and to create a typology of teachers according to their discourse. The study follows two research lines: the first includes thematic analysis of semi-structured interviews with teachers, the second summarizes quantitative data from an expert assessment of teaching observations. In general, the support strategies presented by teachers fall into three groups: 1) instrumental support, 2) relationships, and 3) discipline. Within them, five types of teachers can be identified, which is based on thematic analysis of the interviews. These are confirmed by quantitative data. The teachers' discourse generates specific topics linked to the support of pupils, namely pupils' family background, teachers' reaction to failure, individual approach and personal/professional boundaries. For support strategies to be effective, it is important that the teacher-student relationship provides basic psychological safety.